Prediction of exercise adherence with goal orientations and motivational climate - Ricciardi, Antonio Adrian, author; Butki, Brian, advisor; Lipsey, Tiffany, committee member; Rickard, Kathryn, committee member (Colorado State University. Libraries, 2012)
Decreasing physical activity levels across the nation have aided in the rise of obesity. One reason for this decline in activity is the lack of adherence to exercise programs. Psychological factors such as goal orientations and motivational climates may provide insight into the adherence of exercise. The collegiate population (18-25 years old) at the campus of Colorado State University was sampled in the present study. Individual goal orientations of the subjects were measured using the Task and Ego Orientation in Sport Questionnaire (TEOSQ). Participants were categorized by their individual goal orientations, high task/high ego, high task/low ego, or low task/high ego. Subjects were randomly placed into two groups where they underwent a six-week exercise program with varying motivational climates. The number of attended sessions was greater in the Task/Mastery (T/M) climate compared to the Ego/Performance (E/P) climate (8.84 ± 2.48 to 6.16 ± 2.52, respectively), while the number of missed sessions following exposure to the environment was lesser in the T/M climate, comparatively (3.00 ± 2.43 to 5.53 ± 2.44). Further, task orientation scores were positively correlated with attendance and negatively correlated with missed sessions. Ego orientation scores were in direct contrast revealing negative correlation with attendance and positive correlation with missed sessions. Additionally, individuals with high task/low ego orientation had better adherence outcomes and were the most motivationally adapted group. Lastly, ego scores increased in the E/P climate (3.29 ± 0.92 to 3.7 ± 1.1), while they decreased in the T/M climate (3.33 ± 0.76 to 2.97 ± 0.82). These data provide a greater understanding of the relationship between not only motivational climates and exercise adherence, but also between goal orientations and motivational climates. Task-oriented individuals inherently adhere to exercise programs more easily regardless of the motivational climate compared to ego-oriented individuals. Also, it has become clear that a T/M climate improves exercise adherence outcomes regardless of individual goal orientation based on the finding that dispositional orientations might be altered by the climate provided.
Keywords: adherence; motivational climate; motivation; goal orientation; exercise